Mathematical modeling of ice flow in the north-western Greenland and interpretation of deep drilling data at the NEEM camp - O. O. Rybak; J. J. Fürst; Ph. Huybrechts (Лëд и снег)
The new ice core obtained from the NEEM site in the north-western Greenland (77.449˚N, 51.056˚W, 2447 m a.s.l) in 2008–2012 was expected to improve our knowledge about the Last interglacial (also known as the Eemian, ca. 115 to 130 kyr before present). A numerical modeling, the overview of which is given in this paper, aims at assistance in interpretation of the NEEM ice core. For this purpose, an area of 400 × 400 km was delineated in northwestern Greenland as the domain for the fine-scale model at 2.5 km resolution. Modeled present-day surface velocity was in good agreement with satellite and GPS measurements. The nested ice-sheet model was run over the last two glacial cycles to reconstruct the flow history relevant for interpreting the NEEM ice core. A Lagrangian backtracing procedure was applied to determine the particle trajectories of the ice drilled at the NEEM site. This provides the places of origin at the time of deposition of NEEM ice, from which the ice chronology and non-climatic biases of the records are determined. The latter biases arise from elevation changes of the ice sheet, advection of higher upstream ice, and from latitudinal contrasts in isotopical composition of the ice. These need to be separated from the isotope records to retrieve the climatic signal. In spite of initial expectations, the segment in the NEEM ice core between 2206 m and 2435 m turned out to be heavily disturbed. The presence of high isotope values below 2206 m depth however reveals that there is ice from the previous warm interglacial. Our model locates the EMBED Equation.DSMT4 maximum of the warmest Eemian ice at the right depth (2400 m). On this basis we suggest that the measured contrast between the present and the Eemian EMBED Equation.DSMT4 must be increased by about 1.5 ‰. Most of this non-climatic bias results from upstream advection over an estimated distance of ~175 km. Except for the disturbed section, we are still confident to be able to provide accurate model-based estimates of the ice chronology and non-climatic biases for the core down to ~87% of relative depth. This requires revision the palaeo-accumulation parameterization to better match thinner annual layer thicknesses observed in the ice core for the last glacial period.